2004
DOI: 10.1021/jp0369701
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclopropylmethyl−3-Butenyl Rearrangement on Mo(110):  A Radical Clock on a Surface?

Abstract: The mechanism for the transformation of adsorbed cyclopropylmethyloxide into its ring-opened form, 3-butenyloxide, on the Mo(110) surface is explored theoretically. An alternative emerges to the radical clock mechanism that involves the cleavage of the C-O bond in the adsorbate as the critical reaction step. The alternative pathway involves the cleavage of a C-C bond in the three-membered ring leading to a diradical, which could transform via a 1,2-H shift to the same reaction product. Density functional theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Finally, the three-layer (110) surface model has been widely used in the previous calculations of reactions on the metal surface; for example, Flemmig et al 53 used a three-layer slab Mo(110) surface to investigate the mechanism for the transformation of adsorbed cyclopropylmethyloxide; Classen et al 54 investigated the interaction of trimesic acid with a threelayer slab Cu(110) surface; Wang et al 55 studied the adsorption of CH 3 , CH 3 O, and HCOO on metal Ni using a three-layer slab Ni(110) surface model; Szukiewicz et al 56 employed a three-layer slab Mo(110) surface to investigate the Gd adsorbed layers on the Mo(110) surface; Liao et al 57 used a three-layer slab Rh(110) surface to investigate the adsorption of NO.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Finally, the three-layer (110) surface model has been widely used in the previous calculations of reactions on the metal surface; for example, Flemmig et al 53 used a three-layer slab Mo(110) surface to investigate the mechanism for the transformation of adsorbed cyclopropylmethyloxide; Classen et al 54 investigated the interaction of trimesic acid with a threelayer slab Cu(110) surface; Wang et al 55 studied the adsorption of CH 3 , CH 3 O, and HCOO on metal Ni using a three-layer slab Ni(110) surface model; Szukiewicz et al 56 employed a three-layer slab Mo(110) surface to investigate the Gd adsorbed layers on the Mo(110) surface; Liao et al 57 used a three-layer slab Rh(110) surface to investigate the adsorption of NO.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…119 In addition, the nature of bonding of intermediates to the surface can be analyzed-analogous to a frontier orbital analysis for molecular chemistry-in order to develop predictive frameworks. [120][121][122] Overall, theoretical investigation of the bonding of key surface intermediates, in particular using DFT, is potentially valuable for predicting factors that will change reactions rates and selectivities.…”
Section: Theory and Application Ultrahigh Vacuum Surface Studies To H...mentioning
confidence: 99%
“…Rather than the radical clock process, these authors suggested a diradical mechanism may be operative involving vicinal C-C bond cleavage, and a 1,2-hydrogen atom shift (Scheme 39). 89 The mechanism of vicarious nucleophilic aromatic substitution of hydrogen (direct nucleophilic addition vs. electron transfer) was probed using a cyclopropyl probe in the anion [eqn (18)]. The failure to detect any ring opened products, arising from the rearrangement depicted in eqn 19 was cited as evidence against the electron transfer pathway.…”
Section: Scheme 38mentioning
confidence: 99%